2003
DOI: 10.1111/j.1365-2966.2003.07164.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a high-velocity ionized outflow in a second narrow-line quasar PG 0844+349

Abstract: Following the discovery of X‐ray absorption in a high‐velocity outflow from the bright quasar PG 1211 + 143 we have searched for similar features in XMM–Newton archival data of a second (high accretion rate) quasar PG 0844+349. Evidence is found for several faint absorption lines in both the EPIC and RGS spectra, whose most likely identification with resonance transitions in H‐like Fe, S and Ne implies an origin in highly ionized matter with an outflow velocity of order ∼0.2c. The line equivalent widths requir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
110
1
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 22 publications
13
110
1
1
Order By: Relevance
“…We cannot confirm the strong spectral signatures taken by Pounds et al (2003b) as evidence for high velocity outflow from the source.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…We cannot confirm the strong spectral signatures taken by Pounds et al (2003b) as evidence for high velocity outflow from the source.…”
Section: Discussioncontrasting
confidence: 39%
“…The physical reality of such a structure can only be assessed by an observation yielding high energy data with considerably higher signal to noise; however, if it is real, this absorption structure can be due to a fortuitous combination of outflow velocity and red-shift in the source, or it might be due to hot local gas. This possibility was pointed out by McKernan et al (2004) for the identification of the low energy structures found in the RGS spectra of PG 0844+349 by Pounds et al (2003b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent XMM-Newton observations of bright quasars (Pounds et al 2003a(Pounds et al , 2003bReeves et al 2003) give strong evidence for powerful outflows from the nucleus with mass ratesṀ out $ M yr À1 $Ṁ Edd and velocity V $ 0:1c (i.e., ¼ 0:1) in the form of blueshifted X-ray absorption lines. These outflows closely resemble those recently inferred in a set of ultraluminous X-ray sources with extremely soft spectral components (Mukai et al 2003;Fabbiano et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These objects are: PG 1211+143 (Pounds et al 2003a with an outflow of ∼ 24, 000 km s −1 , PG 0844+349 (Pounds et al 2003b) with an outflow of ∼ 60, 000 km s −1 , and PDS 456 (Reeves et al 2003) with an outflow of ∼ 50, 000 km s −1 . Detection of absorption lines in outflow with grating spectra is of vital importance as one can detect numerous lines in several ions, enhancing the statistical significance of the detection.…”
mentioning
confidence: 99%